Estudio de las necesidades de información generadas por los médicos de atención primaria (proyecto ENIGMA)() - Isabel González-González, Ana (Aten Primaria, 2006)
OBJECTIVES: To determine the information needs of primary care physicians by identifying the frequency and type of questions arising during consultation, and by describing the information-search pattern. DESIGN: Observational, descriptive, multicentre study. SETTING: Primary care practices in Madrid, Spain. PARTICIPANTS: Random sample, proportionally stratified by area (urban/rural) and specialty (general practitioner/paediatrician), of 208 primary care physicians out of a total of 1182 physicians; 112 agreed to take part. INTERVENTIONS: Physicians consultations were video-recorded for four hours. Between patients, they were asked to pose all the clinical questions arising during the patient visit and the sources of information used to answer them. Unresolved questions were followed up by phone 2 weeks later to check if answers had been found and what sources of information had been used. Clinical questions were classified by topic and type. Main measurements. Number of questions posed and their answers; topic and type of information; information resources used. RESULTS: A total of 3511 patient consultations, leading to 635 clinical questions, were recorded. The most frequent questions were on pharmacology (10%) for general practitioners, and infectious disease (19%) for paediatricians. The most frequent type of question was on the cause/interpretation of a clinical finding (44% for general practitioners and 48% for paediatricians). Answers to 39% of the questions were not sought. A 86% of the answers sought were solved, mainly using the drug compendium (35%) or a text-book (18%). CONCLUSIONS: Primary care physicians tried to resolve less than two-thirds of the questions asked, and mainly did so through readily available printed material. Better methods are needed to provide answers to questions that arise in clinical practice.